Genetic diversity of rice sheath blight in different geographical regions of China: Genetic diversity of rice sheath blight - Tian, Li; Wang, Chun; Li, Hailiang; Sun, Haitian (Cellular and Molecular Biology, 2022)
Rhizoctonia solani AG1-IA (Thandfephorus cucumeris teleomorph) is the causative agent of rice sheath blight in Chinese paddy fields. Due to the importance of the disease and the lack of comprehensive information on the genetic structure of the fungus populations, 25 isolates collected from Hubei, Sichuan, Anhui, and Jiangsu provinces, and southern China’s Yangtze River basin were examined for morphological characteristics, growth rate, and genetic diversity of this pathogen. The anastomosis group determination test results showed that all isolates belong to the AG1-IA anastomosis group. To quickly diagnose and confirm the anastomosis group of isolates, ten isolates along with AG1-IA and AGA standard isolates were examined by specific primers AG1-IA. A 256bp band was amplified in all of them. The results of the growth velocity study divided the isolates into two groups’ fast growth (68% of isolates) and slow growth (32% of isolates). The genetic diversity of 25 isolates was assessed using the RAPD marker. Among the 20 primers, bands from seven primers ranging from 250 to 5,000bp were performed using the Jaccard similarity coefficient and UPGMA method by data cluster analysis of NTSYS-pc software. The cluster analysis results divided the isolates into two groups with a similarity level of 36%, which corresponded to the grouping of isolates into two groups of fast growth and slow growth. At the level of 80% similarity, the isolates were divided into 23 groups, which indicate the high genetic diversity of these isolates. The results of the molecular analysis showed that isolates belonging to a geographical area do not necessarily have a genetic affinity. This study performed rapid detection of R. solani AG1-IA using specific primers AG1-IA, and evaluation of genetic diversity of rice sheath blight isolates was performed by RAPD marker in this study.